Determinant of Post COVID-19 Vaccination (Sinovac) Adverse Events Among Health Care Workers in Palembang - Mustika Fatimah; Dianita Ekawati; Rico Januar Sitorus; Supli Effendi Rahim; Alfredo Armando Parensyah (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2022)
The COVID-19 cases in Palembang are still increasing every day. This pandemic has forced the adaptation of the